O Maceió Shopping como nova centralidade no espaço urbanoS - Lins, Lívia Menezes das Neves (2018)
The shopping malls, while business in general and services have been expanding around the world since 1950 and in Brazil more intensively in the 1980s. However, its role in the spatial organization of the city has been highlighted in the places where they were implemented, they promoted new spatial rearrangements and in many cases an urban restructuring, due to the centrality it generates and the consequent valorization of the area that was inserted. The objective of this research was to analyze how this process occurred in the city of Maceió since the inauguration of Maceió Shopping in 1989, in an area of very low population density of a mononucleated city. To do so, we have made a reflection based on the role that the center plays in the city in its historical context and in the conceptual differences between center and centrality, with emphasis on flows and fixed as fundamental elements to make this distinction. Next, we evaluate the polycentralities, represented here by the shopping malls, as promoters of valorization and developments of the areas in which they are inserted in the city and its restructurating power. This discussion permeated the construction of a technosphere linked to a psychosphere where society has as its pillar of support consumerism, the shopping center being a technical object created for this purpose. We analyze the different aspects of this type of commercial enterprise in the United States, Europe and Brazil, highlighting specificities that favor this sector in our country, such as urban violence and the deterioration of traditional centers. We evaluate the role of real estate agents and the state regarding their actions in the areas where shopping centers are located. Having exposed all this panorama we began to analyze how the insertion of the first shopping center in the city of Maceió took place, we followed the same path traced in the theoretical discussion when we started identifying the origin of the first center of the city and how it was structured from it, as it happened the decentralization process and the emergence of new centralities (subcentres) linked to population growth and the expansion of the urban network that was driven by the verticalization process, production of horizontal condominiums, popular housing complexes and irregular occupations in subnormal areas.This exposed, we arrived at our object of study, the Maceió Shopping, we evaluated the impact that its insertion in the urban space caused in the pre-established territorial organization. To do so, we have information provided by the management of the shopping center through open interviews and data collected through the application of semi-structured questionnaires with their customers. To show the impact caused by it in the city, we made a survey with the SMTT regarding the distribution and route of bus lines, as they are responsible for driving the large flow of people in the city. The analysis was done before and after the inauguration of Maceió mall and we verified with the results evidenced in the maps that the city was restructured from being mononucleated to become polinucleda due to the emergence of new poles generating flow of people linked to the new centrality that reorganized the urban spatial dynamics, this undertaking being the second largest generator pole, after the Center, for its spatial reach to the city and for promoting a flow of conversion and daily dispersion of people.